Direct Measurements of Laser Communication Point-Ahead Angles from the Artemis Geostationary Satellite Through Clouds - Kuzkov, V.P.; Sodnik, Z.; Kuzkov, S.V. (Science and Innovation, 2024)
Laser experiments with ARTEMIS geostationary satellite have been performed in partly cloudy weather using the developed system for the telescope. It has been found that the part of the laser beam is observed simultaneously at the points in direction of the velocity vector where the satellite would arrive at when the laser light reaches the telescope. These results agree with the theory of relativity for light aberration in transition from fixed to moving coordinate system. Observation results open the way for research and development of systems to compensate atmospheric turbulence in laser communications between ground stations and satellites through the atmosphere.